Realization of Principles of the Basic World Tax Code in Russian Tax System - O. A. Borzunova (Московский журнал международного права, 2009)
Globalization, internationalization, integration are a tendency of development of economics and law. Tax law is not an exception in this process. World community tries to unify norms of tax law, to implement a united tax policy, which promotes free transaction of goods, services and financial assets. Basic World Tax Code (BWTC) is one of such universal world instrument; its implementation is developed in this article.The author emphasizes Russia exercised many norms of Basic world tax code in the Tax Code of Russian Federation.